Development of new sustainable construction materials using by-product sulfur and other industrial by-products in Kazakhstan - Kim, J.R.; Saliyev, D.; Zhumabekov, G.; Bakhtiyarov, D. (Nazarbayev University, 2013)
The objectives of this project are: 1) to develop new sustainable construction materials using the by-product sulfur and other industrial by-products with special emphasis on long term production of the modified sulfur concrete; and 2) to investigate its potential for use in concrete with satisfying both fresh and hardened properties and providing satisfactory durability performance with respect to deterioration mode of sulfur concrete structure exposed to Kazakhstan’s severe environmental condition such as the combination of freezethaw (F–T) and chloride ion diffusion conditions.
Keywords: first research week; by-product sulfur; oil and gas industry